Computational Thinking and Metacognition of Preservice Teacher Students in Digital Technology - Philuek, Wudhijaya; Janyarat, Sirirat; Kittisunthonphisarn, Nattapakal (SOCIAL SCIENCES RESEARCH AND ACADEMIC JOURNAL, 2025)
This research aimed to study the level of computational thinking and metacognition of digital technology for education preservice teachers’ students. The quantitative research was conducted by surveying the target group, which was 151 students in the Bachelor of Education Program in Digital Technology for Education, the Faculty of Education, Nakhon Sawan Rajabhat University, who were students in the second semester of the academic year 2024. Of these, 99 students responded to the questionnaire/assessed within the specified period. The data collection tools consisted of 1) the computational thinking assessment form (Junpho et al., 2022), with a reliability of .941, and 2) the metacognition assessment form of Pedone et al. (2017), with a reliability of .957. The statistics used for data analysis included Mean, Standard Deviation, Independent t-test, One-Way Analysis of Variance, and Pearson’s correlation coefficient. The research results found that: 1. There were statistically significant differences between gender and some variables of computational thinking and metacognition of students. 2. There were statistically significant differences between the students’ academic year and some variables of computational thinking and metacognition. 3. There were no statistical differences in academic performance on the variables of computational thinking and metacognition. 4. The result of the analysis of the relationship of 36 pairs of computational thinking and metacognition variables found that 1 pair was not related and 35 pairs were related with a rage of .242 to .752, 34 pairs have a significance level of .01 and 1 pair has a significance level of .05 that all pairs were positively related.